2016
DOI: 10.1186/s12904-016-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between different opioid doses and the survival of advanced cancer patients receiving palliative care

Abstract: BackgroundConcerns that opioids may hasten death can be a cause of the physicians’ reluctance to prescribe opioids, leading to inadequate symptom palliation. Our aim was to find if there was an association between different opioid doses and the survival of the cancer patients that participated in our palliative care program.MethodsA retrospective study was conducted at Ramathibodi Hospital, Bangkok between January 2013 and December 2015. All of the cancer patients that were referred to palliative care teams by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Three patients (19%) receiving end-of-life care with an underlying oncology diagnosis died within 7 days of commencing methadone. Previous studies have found use of opioids in palliative care does not hasten death; these three deaths were attributed wholly to underlying disease processes [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three patients (19%) receiving end-of-life care with an underlying oncology diagnosis died within 7 days of commencing methadone. Previous studies have found use of opioids in palliative care does not hasten death; these three deaths were attributed wholly to underlying disease processes [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective study included 317 cancer patients. They showed that different doses of opioids were not associated with a shortened survival period (p = 0.52) [95].…”
Section: Opioids and Clinical Datamentioning
confidence: 98%
“…And yet, most evidence worldwide suggests that opioids used to manage pain in palliative care do not hasten death. [4][5][6][7][8][9] Even when titrated to avoid distress in ventilation withdrawal, opioids do not shorten life. 10 These contradictory views exist because of the false perception that opioids are dangerous in all situations.…”
Section: The Myth That Shames Us Allmentioning
confidence: 99%